Nonlinear characteristics of Cr2O3, WO3, ZnO and CoO doped SnO2 varistors - Margionte, MAL; Simoes, A. Z.; Riccardi, C. S.; Ries, A.; Filho, F. M.; Perazolli, L.; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
SnO2 based ceramics doped with 1.0 mol% ZnO, 1.0 mol% CoO, 0.1 mol% WO3 and 0.05 mol% Cr2O3 show varistor behavior with nonlinear coefficient alpha = 33, breakdown electric field E-B = 12.5 kV/cm, leakage current I = 0.63 mA/cm(2) and average grain size of 1.52 mu m. Experimental evidence shows that the addition of Cr2O3 improves the nonlinear properties of the samples significantly, the impedance data, represented by means of Nyquist diagrams, show a dramatic increase in the resistivity for the samples doped with Cr2O3. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: sintering; tin oxide; dopants; varistors